Odpowiedzi

Najlepsza Odpowiedź!
2009-10-11T10:15:04+02:00
C) (2x-1)(2x+1) +6 = 4(x-4) do kwadratu + 3x
(4x²-1) +6 = 4(x-4)²+3x
4x²-1+6 = 4(x²-8x+16)+3x
4x²+5=4x²-32x+64+3x
4x²-4x²+5-64=-29x
-59=-29x/:(-29)
x= 59/29= 2 1/29

d) (4x+3) do kwadratu +10 = (4x-1)(4x+1) +4x
(4x+3)²+10=(16x²-1)+4x
16x²+24x+9+10= 16x²-1 +4x
16x²-16x²+24x-4x+19+1=0
20x+20=0
20x=-20/:20
x = -1


20.
a) (x-5) do kwadratu - 2 = x(x-2) - x-1 to x-1 to ma byc ułamaek czyli x-1/2
(x-5)²-2= x²-2x-(x-1)/2/mnożymy przez 2
2(x²-10x+25)-4=2x²-4x-(x-1)
2x²-20x+50-4=2x²-4x-x+1
2x²-2x²-20x+5x+46-1=0
-15x+45=0
-15x=-45/:(-15)
x=3

2009-10-11T10:23:17+02:00
4x+2x-2x-4xkwadrat-3x=-64+1-6
-2x=-69/-2
x=34,5